A possible solution to minimise scotta as a food waste: A sports beverage. (11th September 2019) - Tirloni, Erica; Vasconi, Mauro; Cattaneo, Patrizia; Moretti, Vittorio; Bellagamba, Federica; Bernardi, Cristian; Stella, Simone
Abstract : A pilot study trial was performed on ready‐to‐drink beverages produced in a small‐scale dairy plant starting from Ricotta whey (scotta) with the addition of fruit puree and starter cultures. Microbiological shelf life was evaluated at 4 and 12 °C. At 4 °C, the product showed moderate total viable counts until the end of the trial (~5 log cfu/mL). Yeasts proved to be the specific spoilage microorganisms of the product. When applying a thermal abuse at 20 °C for 6 h, total viable count did not increase. The addition of fruit puree changed the volatile profile of the beverages compared to raw scotta.